Co-educational adult homemaking in Wisconsin city vocational schools - Miller, Ruth Rick, author; Morgan, David H., advisor; Avery, George T., committee member; Williamson, Maude, committee member; Kinyon, Kate Pamela Woodard, 1881-, committee member; Betts, Gilbert L., committee member; Rice, Juanita, committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Adult education; Vocational education -- Wisconsin; Home economics -- Study and teaching -- Wisconsin